Projeto colaborativo em ambientes digitais de atividades de aprendizagem e avaliação para aquisição de competências em informação e documentação - Del Carmen Agustín-Lacruz, Maria; Gómez-Díaz, Raquel; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2011)
The search for international impact and the need to create formal or informal networks of academic cooperation are some of the most common features of the current training offered by many universities. Aware of this difficulty and the desirability of creating synergies to enrich teaching and academic collaboration networks between universities, an experience is presented, in the context of the teaching of Information and Documentation, of inter-university collaboration for the joint design of learning activities and skills assessment, developed by teachers in the public universities of Zaragoza and Salamanca (Spain) and the São Paulo Universidade Estadual Paulista Júlio de Mesquita Filho (São Paulo, Brazil). The experience is developed using models that facilitate the structuring of learning activities aimed at the acquisition of common skills. Each activity that is proposed and developed is recorded in a spreadsheet which collects the information arranged in various fields such as: description, skills, objectives, expected learning outcomes, tools, required resources and materials, evaluation criteria, amongst others, so that the student can see what he is asked to do, how to do it and how useful it will be. This way of designing skills-based learning activities is possible, in geographically diverse academic settings through the use of Information Technology and Communication, enabling both remote cooperation between teachers and also materials offered on the platforms of each of the universities.
Joint project in digital learning environments and an evaluation in obtaining information and documentation skills
Keywords: Competence based learning; Design of learning activities; European higher education area; Information technology and communication